Regreening of The Northern Ethiopian Mountains: Effects on Flooding and on Water Balance - Asfaha, Tesfaalem G.; De Meyere, Michiel; Frankl, Amaury; Haile, Mitiku; Nyssen, Jan (Afrika Focus, 2019)
The hydro-geomorphology of mountain catchments is mainly determined by vegetation cover. This study was carried out to analyse the impact of vegetation cover dynamics on flooding and water balance in 11 steep (0.27-0.65 m m-1) catchments of the western Rift Valley escarpment of Northern Ethiopia, an area that experienced severe deforestation and degradation until the first half of the 1980s and considerable reforestation thereafter. Land cover change analysis was carried out using aerial photos (1936,1965 and 1986) and Google Earth imaging (2005 and 2014). Peak discharge heights of 332 events and the median diameter of the 10 coarsest bedload particles (Max10) moved in each event in three rainy seasons (2012-2014) were monitored. The result indicates a strong reduction in flooding (R2 = 0.85, P<0.01) and bedload sediment supply (R2 = 0.58, P<0.05) with increasing vegetation cover. Overall, this study demonstrates that in reforesting steep tropical mountain catchments, magnitude of flooding, water balance and bedload movement is strongly determined by vegetation cover dynamics. KEY WORDS: HYDRO-GEOMORPHOLOGY, REFORESTATION, CREST STAGE, PEAK DISCHARGE, BEDLOAD